ENT 530 Social Media Portfolio / Nurul Asyiqin Idris - Idris, Nurul Asyiqin (2019)
This business name is Yankee Fruity. This business opened when I have been asking to complete my individual project which is online business that requires student to open a Facebook page. Before that, I registered my business with Suruhanjaya Syarikat Malaysia (SSM) under the name of NURUL AS YI QIN 131NTI IDRIS. The registration number for this business is 003033993-A. Registered location of my business is a LOT 6444 JALAN SURAU SEBA YA , KG BUKIT KAPAR 42200 KAPAR, SELANGOR. Any information or detail can contact this number 011-61189781 According to this business, I was assign to the media social as a medium to gain knowledge and information in entrepreneur life. This is because, this subject are very competitive and expose me to the real world of the entrepreneur life.